Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write terhadap Keterampilan Komunikasi Siswa Kelas V Sekolah Dasar - Citra Lestari; Nurmayani Nurmayani; Ibrahim Gultom; Sorta Simanjuntak; Faisal Faisal (FKIP, Universitas Palangka Raya, 2024)
The problem in this study is that the learning carried out in grade V SD Negeri 104203 Bandar Khalipah has not fully provided opportunities for students to construct and communicate their ideas, ideas, or opinions orally and in writing, in the social studies content of the material